Penanganan Risiko Jatuhan Batu Dengan Simulasi Jatuhan Batuan (Studi Kasus Di Kloch) - Frans Tohom; Ari Sandyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Rockfalls are a natural and dynamic geologic process and is common in mountainous areas near cliffs of broken, faulted, or jointed bedrock, on steep slopes of rocky soils, or where cliffy bedrock ledges are undercut by erosion or human activity. Simulation of rock falls, along with analyzing kinetic energy and bounce height, can result in providing protection measures in the right places with the least costs. In this study, slopes that were analyzed is a manmade slope in quarry at Kloch, Austria.   Three different construction alternatives or barrier were then proposed:(i) constructing of a catchfences with a capacity to restrain the rockfall energy about 100 - 5000 kJ, (ii) construction of concrete barrier with the capacity up to 100 kJ, and (iii) construction of a wooden retaining wall with the capacity up to 30 kJ. Keywords: Simulation, Rockfall, barriers, slope